Influence of clinical experience on accuracy and safety of obliquus capitus inferior dry needling in unembalmed cadavers. (2nd December 2022) - Kearns, Gary A.; Hooper, Troy L.; Brismée, Jean-Michel; Allen, Brad; Lierly, Micah; Gilbert, Kerry K.; Pendergrass, Timothy J.; Edwards, Deborah
ABSTRACT: Background: Suboccipital myofascial trigger points are common in tension-type headaches. Objectives: Compare the influence of clinical experience on the accuracy and safety of dry needle placement on the C2 laminar arch using a cranial-medial and caudal-medial technique to target obliquus capitus inferior in unembalmed cadavers. Methods: Three physical therapists inserted three 50 mm dry needles, per technique, individually toward the C2 laminar arch targeting the obliquus capitus inferior. Ultrasound video of each trial was recorded, and an investigator trained in ultrasound interpretation and blinded to experience level recorded needling accuracy. Results: The novice, experienced and expert clinicians were accurate on 73.8%, 59.5% and 71.4% of caudal-medial trials, and 14.3%, 16.7% and 66.7% of cranial-medial trials, respectively, with each clinician striking the spinal cord at least once. The expert clinician was 10 times more likely to accurately reach the C2 laminar arch using the cranial-medial direction than the experienced and novice clinicians. Conclusion: Increased clinical experience improved accuracy reaching the C2 laminar arch, with all investigators being more accurate with the caudal-medial technique. Greater experience did not eliminate risk as all investigators recorded at least one incident of striking the spinal cord. Fewer spinal cord strikes occurred with the cranial-medial than the caudal-medial technique.